Charged off Great Speeches for Better Speaking : Listen and Learn from History's Most Memorable Speeches - Eidenmuller, Michael E. (New York McGraw-Hill, 2008)
What person faced with speaking in public wouldn't want some pointers from great speakers like John F Kennedy or Ronald Reagan? This work outlines the six areas that are critical for making an impact with a speech - situation, content, structure, style, delivery, rhetorical strategies and tactics. It also features six speeches on an audio CD.
Include Glossary and References
CIV/MSL/US/03 of 30 Aug 2019
Keywords: Public speaking